2008
DOI: 10.1080/10401230802017092
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia: A Review

Abstract: Catatonia is a common disorder that occurs in a wide variety of psychiatric, neurological and medical conditions. At the current time, there is sufficient evidence to consider it as a specific nosologic syndrome with different subtypes and treatment responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 95 publications
1
32
0
16
Order By: Relevance
“…1,5,6,23 Both the ICD-10 and the DSM-IV list catatonic schizophrenia as a subtype of schizophrenia; DSM-IV, however, also includes catatonic symptoms in other categories and states that catatonic symptoms occur more frequently in the context of mood disorders than schizophrenia. The ICD-10 contains a category for organic catatonic disorders and also includes ''stupor'' as a feature of several other categories; stupor in the ICD-10 has many features in common with psychomotor disturbances seen in catatonia.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6,23 Both the ICD-10 and the DSM-IV list catatonic schizophrenia as a subtype of schizophrenia; DSM-IV, however, also includes catatonic symptoms in other categories and states that catatonic symptoms occur more frequently in the context of mood disorders than schizophrenia. The ICD-10 contains a category for organic catatonic disorders and also includes ''stupor'' as a feature of several other categories; stupor in the ICD-10 has many features in common with psychomotor disturbances seen in catatonia.…”
Section: Discussionmentioning
confidence: 99%
“….). 1,2 En las últimas décadas, la incidencia de la catatonia se ha visto reducida, y se cree que ello en parte es debido a un infra-diagnóstico de dicho síndrome, lo que hace pensar que los profesionales no lo tenemos presente. 3 Cabe recordar que en algunos casos puede llegar a causar la muerte, por lo que es muy importante realizar un diagnóstico precoz para aplicar lo antes posible el tratamiento adecuado.…”
Section: Introductionunclassified
“…3 Cabe recordar que en algunos casos puede llegar a causar la muerte, por lo que es muy importante realizar un diagnóstico precoz para aplicar lo antes posible el tratamiento adecuado. [2][3][4] …”
Section: Introductionunclassified
“…Catatonia is a very serious, potentially lethal condition that is not easy to study using well-controlled designs. The review articles indicated general agreement that benzodiazepines and electroconvulsive therapy are the treatments of choice for acute and maintenance treatment of catatonia (Carroll et al 2007 ;Manjunatha et al 2007 ;Ungvari et al 2001 ;Weder et al 2008 ) . The benefi cial use of benzodiazepines to treat catatonia has been described in some patients with IDs (Dent 1995 ;Fink et al 2006 ;Gaind et al 1994 ;Kakooza-Mwesige et al 2008 ) .…”
mentioning
confidence: 96%